Profesionalisme Guru Pendidikan Agama Kristen Di Era Pandemi Covid-19 - Ranting, Hermin; Purwantoro, Elia; E Sipayung, Gerhard; Ginting, Gundari (PT. Bangun Harapan Bangsa, 2022)
The Covid-19 pandemic has changed the entire order of life, including in the field of education, which requires the world of education to update the abilities of a teacher in their respective places. With these demands, teachers must update their abilities in all areas specifically in skills, learning methods and learning materials and character. It is done as a reference for teachers to prove qualified abilities. Using a qualitative method of literature study approach, this article presents a finding related to how professional Christian teachers should be. The findings in this article suggest that there are many things that must be considered in carrying out duties and responsibilities as a teacher during the COVID-19 pandemic. This is done in order not to reduce the quality in carrying out its duties and responsibilities properly. With the teacher upgrating his abilities in all aspects, it is part of the tangible manifestation of a teacher's professionalism. That attitude of professionalism is a must for a teacher, considering that the current era is closely related to digitalization.